Genetic ancestry and radical prostatectomy findings in Hispanic/Latino patients - Acosta-Vega, Natalia L.; Varela, Rodolfo; Mesa, Jorge Andrés; Garai, Jone; Gómez-Gutiérrez, Alberto; Serrano-Gómez, Silvia J.; Zabaleta, Jovanny; Sanabria-Salas, María Carolina; Combita, Alba L. (Frontiers in Oncology, 2024)
African ancestry is a known factor associated with the presentation and aggressiveness of prostate cancer (PC). Hispanic/Latino populations exhibit varying degrees of genetic admixture across Latin American countries, leading to diverse levels of African ancestry. However, it remains unclear whether genetic ancestry plays a role in the aggressiveness of PC in Hispanic/Latino patients. We explored the associations between genetic ancestry and the clinicopathological data in Hispanic/Latino PC patients from Colombia.We estimated the European, Indigenous and African genetic ancestry, of 230 Colombian patients with localized/regionally advanced PC through a validated panel for genotypification of 106 Ancestry Informative Markers. We examined the associations of the genetic ancestry components with the Gleason Grade Groups (GG) and the clinicopathological characteristics.No association was observed between the genetic ancestry with the biochemical recurrence or Gleason GG; however, in a two groups comparison, there were statistically significant differences between GG3 and GG4/GG5 for European ancestry, with a higher mean ancestry proportion in GG4/GG5. A lower risk of being diagnosed at an advanced age was observed for patients with high African ancestry than those with low African ancestry patients (OR: 0.96, CI: 0.92-0.99, p=0.03).Our findings revealed an increased risk of presentation of PC at an earlier age in patients with higher African ancestry compared to patients with lower African ancestry in our Hispanic/Latino patients.